Repeat endocarditis: analysis of risk factors based on the International Collaboration on Endocarditis – Prospective Cohort Study. (11th November 2013) - Alagna, L.; Park, L. P.; Nicholson, B. P.; Keiger, A. J.; Strahilevitz, J.; Morris, A.; Wray, D.; Gordon, D.; Delahaye, F.; Edathodu, J.; Miró, J. M.; Fernández‐Hidalgo, N.; et al.
Abstract Repeat episodes of infective endocarditis (IE) can occur in patients who survive an initial episode. We analysed risk factors and 1‐year mortality of patients with repeat IE. We considered 1874 patients enrolled in the International Collaboration on Endocarditis – Prospective Cohort Study between January 2000 and December 2006 (ICE‐PCS) who had definite native or prosthetic valve IE and 1‐year follow‐up. Multivariable analysis was used to determine risk factors for repeat IE and 1‐year mortality. Of 1874 patients, 1783 (95.2%) had single‐episode IE and 91 (4.8%) had repeat IE: 74/91 (81%) with new infection and 17/91 (19%) with presumed relapse. On bivariate analysis, repeat IE was associated with haemodialysis (p 0.002), HIV (p 0.009), injection drug use (IDU) (p < 0.001), Staphylococcus aureus IE (p 0.003), healthcare acquisition (p 0.006) and previous IE before ICE enrolment (p 0.001). On adjusted analysis, independent risk factors were haemodialysis (OR, 2.5; 95% CI, 1.2–5.3), IDU (OR, 2.9; 95% CI, 1.6–5.4), previous IE (OR, 2.8; 95% CI, 1.5–5.1) and living in the North American region (OR, 1.9; 95% CI, 1.1–3.4). Patients with repeat IE had higher 1‐year mortality than those with single‐episode IE (p 0.003). Repeat IE is associated with IDU, previous IE and haemodialysis. Clinicians should be aware of these risk factors in order to recognize patients who are at risk of repeat IE.